Nikah Misyar Perspektif Yusuf Qardhawi Dan Dosen Prodi Ahwal Syakhshiyah STAI Jam’iyah Mahmudiyah Tanjung Pura - Deny Ramadhany (Journal Smart Law, 2023)
Marriage is one of the Islamic laws to protect oneself from adultery, and aims to build a family that is sakinah, mawaddah, warohmah. However, as time goes by, more and more women are choosing careers until they are past the ideal age for marriage, whereas as a normal woman she still has lust and needs to channel it, so the misyar marriage emerged. Misyar marriage is a marriage where the woman is willing to give up some of her rights and not live at home with her husband. There are several opinions of scholars regarding misyar marriage. There are scholars who forbid it, such as Sheikh Muhammad Nashirudin Albani, Ali Qurah Daqi, Wahbah Zuhaili and Abdul Sattar Jubali, and there are those who make it halal, one of whom is Yusuf Qardhawi. Because of this debate, the author felt interested in conducting research on misyar marriage from the perspective of Yusuf Qardhawi and Lecturers in the Ahwalus Syakhsiyah Study Program at STAI Jam'iyah Mahmudiyah Tanjung Pura because as teaching staff in the field of Islamic law, of course they really understand Islamic law. The results of the research explain that Yusuf Qaradawi is of the opinion that misyar marriage is permissible because the conditions and pillars have been fulfilled, and a woman is allowed to give tanazul (relief) from some of her rights and at the same time honor and guard against slipping into the act of adultery. Lecturer at the Ahwal Syakhshiyah Study Program at STAI Jam'iyah Mahmudiyah Tanjung Pura is of the opinion that misyar marriages are haram because they are not in accordance with Islamic law and the laws in force in Indonesia. In a misyar marriage, the husband does not give rights that the wife must accept, while in Islam the rights and obligations between husband and wife are regulated in such a way and must be carried out. The opinion chosen is the opinion of the Ahwal Syakhshiyah Study Program Lecturer at STAI Jam'iyah Mahmudiyah Tanjung Pura who forbids misyar marriage seeing that the dangers are greater than the benefits. Also remember that marriage is not just about fulfilling biological desires. There is a lot that must be done to become a family that is sakinah, mawaddah, wa rahmah as the goal of marriage.